Beyond Covid: Pandemics and the Economics of Aging and Longevity - Holger Strulik; Volker Grossmann (CESifo GmbH, 2024)
In this paper, we examine the effects of the Covid-19 pandemic on individual aging and longevity with special focus on socioeconomic disparities in health outcomes. We also explore the individual-specific effects of Long Covid. We develop and calibrate a health economic model based on principles of the biology of human aging that captures the interaction between infections and chronic health deficits. Our analysis suggests that neglecting this interaction leads to a gross underestimation of the long-term health impact of the pandemic. Our model also explains large socioeconomic health differences that can be attributed to infection protection behavior.
Keywords: D15; I10; I12; J24; J26; 330; Covid-19; Long Covid; health behaviour; health deficits; health inequality; protection aversion; false beliefs; longevity